Design and analysis of stair-shape UWB antenna with flowery DGS. Issue 1 (February 2015) - Kaur, Sukhdeep; Khanna, Rajesh
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper, staircase-shaped ultra-wideband (UWB) response is proposed. UWB technology being emerging technology of decade needs development of antennas with small size. This paper proposed the design of antennas for UWB technology with small overall size. The feed used in the proposed design is microstrip feed line. The defected ground structure and staircase patch have been used to enhance bandwidth (BW) of antenna, to miniaturize its shape and to reduce the surface wave. The proposed design is carried out with different types of substrate materials and the best results are considered. The proposed antenna performs well in terms of BW and gain while reduction in size is reported. The proposed antenna can be used for Wireless Personal Area Network.